Laughter yoga reduces the cortisol response to acute stress in healthy individuals. (2nd January 2021) - Meier, Maria; Wirz, Lisa; Dickinson, Philip; Pruessner, Jens C.
Abstract: Stress is one of the foremost contributors to the development of psychiatric diseases. Since the prevalence of stress-related complaints is increasing, we are in need for affordable and effective treatment alternatives. Laughter yoga (LY), a popular method encouraging participants to simulate laughter and participate in yogic breathing exercises, is hypothesized to buffer negative effects of stress. Although widely practiced, empirical evidence for beneficial effects of LY is scarce. We investigated the acute effects of a single 30-min LY session on the autonomic, endocrine and psychological response to a standardized psychosocial stressor. Thirty-five healthy subjects (51% female) were randomly assigned to experience either a LY ( n = 11), a relaxation breathing ( n = 12) or a (non-intervention) control ( n = 12) session prior to their exposure to the Trier Social Stress Test for Groups (TSST-G). Salivary cortisol, salivary alpha amylase, and subjective stress were assessed repeatedly throughout the experiment. We expected that LY and relaxation breathing group each show a downregulation of stress response indices compared to the control group. Further, we expected that LY has beneficial effects compared to relaxation breathing. The groups did not differ in salivary cortisol, alpha amylase or subjective stress reactivity during the 30-min intervention. However, in response to the TSST-G, the LY, but neither the relaxation breathing, nor the control condition, showed an attenuated cortisol stress response. These findings highlight the potential of LY to buffer the endocrine stress response. Therefore, LY could be used as a cheap and easily-to-implement add-on to more traditional stress interventions. LAY SUMMARY: In recent years, more and more people have reported to feel stressed. Although our body is well equipped to deal with acute stress, chronic stress can tire our system and contribute to illness in the long run. Therefore, we need affordable and effective measures to reduce stress. In this study we have investigated whether a single laughter yoga session can help us to deal with acute stress. Although laughter yoga did not change how stressful a situation was perceived, it reduced the amount of stress hormones that were released in response to the situation. As such, laughter yoga might be a cheap and easily-to-implement add-on to more traditional stress reduction interventions.